Curcumin as an Alternative Epigenetic Modulator: Mechanism of Action and Potential Effects - Hassan, Faiz-ul; Rehman, Muhammad Saif-ur; Khan, Muhammad Sajjad; Ali, Muhammad Amjad; Javed, Aroosa; Nawaz, Ayesha; Yang, Chengjian (Frontiers in Genetics, 2019)
Curcumin (a polyphenolic compound in turmeric) is famous for its potent anti-inflammatory, anti-oxidant and anti-cancer properties, and has a great potential to act as an epigenetic modulator. The epigenetic regulatory roles of curcumin include the inhibition of DNA methyltransferases (DNMTs), regulation of histone modifications via the regulation of histone acetyltransferases (HATs) and histone deacetylases (HDACs), regulation of microRNAs (miRNA), action as a DNA binding agent and interaction with transcription factors. These mechanisms are interconnected and play a vital role in tumor progression. The recent research has demonstrated the role of epigenetic inactivation of pivotal genes that regulate human pathologies such as cancers. Epigenetics helps to understand the mechanism of chemoprevention of cancer through different therapeutic agents. In this regard, dietary phytochemicals, such as curcumin, have emerged as a potential source to reverse epigenetic modifications and efficiently regulate the expressions of genes and molecular targets that are involved in the promotion of tumorigenesis. The curcumin may also act as an epigenetic regulator in neurological disorders, inflammation and diabetes. Moreover, curcumin can induce the modifications of histones (acetylation/deacetylation), which are among the most important epigenetic changes responsible for altered expressions of genes leading to modulating the risks of cancers. Curcumin is an effective medicinal agent, as it regulates several important molecular signaling pathways that modulate survival, govern anti-oxidative properties like nuclear factor E2-related factor 2 (Nrf2) and inflammation pathways e.g., nuclear factor kappa B (NF-κB). Curcumin is a potent proteasome inhibitor that increases p-53 level and induces apoptosis through caspase activation. Moreover, the disruption of 26S proteasome activity induced by curcumin through inhibiting DYRK2 in different cancerous cells resulting in the inhibition of cell proliferation opens up a new horizon for using curcumin as a potential preventive and treatment approach in proteasome-linked cancers. This review presents a brief summary of knowledge about the mechanism of epigenetic changes induced by curcumin and the potential effects of curcumin such as anti-oxidant activity, enhancement of wound healing, modulation of angiogenesis and its interaction with inflammatory cytokines. The development of curcumin as a clinical molecule for successful chemo-prevention and alternate therapeutic approach needs further mechanistic insights.